A omissão inconstitucional na jurisprudência do Supremo Tribunal Federal - Silva, Caio Cesar Guzzardi da (2011)
The objective of this work is to study theories about the effectiveness and applicability of the constitutional law and to ascertain the treatment of omission unconstitutional by the Supreme Court. Also, is to review the efficiency or inefficiency of the legal instruments that seek to ensure maximum effectiveness of the constitution. The hypothesis is that there is a gap between the protection against the normative omission and the non-normative omission, which sets the program standards to a higher risk of remaining devoid of effectiveness. The conclusion is that the constitutional system is in need of access mechanisms to eliminate, by jurisdiction, the unconstitutional non-normative omission